Dynamic Relationship Between Energy and Economic Growth: Evidence from D8 Countries. (The Pakistan Development Review, 2011)
Energy sector has a vital influence on an economy, on both demand and supply sides. Therefore, energy production and consumption bear great importance for the developing world. The oil embargo of 1970‘s and its impact on major macroeconomic variables throughout the world attracted many economists to examine the relationship between energy and economic prosperity. The researchers have been unable to establish a definitive direction of causality between the two variables. The purpose of this study is to empirically investigate the dynamic relationship between energy use and economic growth in the D8 countries. The evidence gathered through application of VAR Granger Causality, Johansen Cointegration and VECM proves existence of short-run and long-run correlation between energy use and economic development in all countries. The results supported either uni-directional or bi-directional causality in the D8 countries except for Indonesia in short-run where non-causality was established between the two variables. JEL classifications: C22; Q43. Keywords: Energy Use, Economic Growth, D8, VAR Granger Causality, Cointegration, VECM